Effect of GIC Neutral Blocking Devices (NBDs) on Power Network Ferroresonance in Malaysia - Khurshid Z.M.; Ab Aziz N.F.; Rhazali Z.A.; Ab Kadir M.Z.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Computer aided analysis; Computer aided design; Electric fault currents; Electric grounding; Electric network analysis; Electric power transmission networks; Magnetic resonance; Metals; Outages; Power transformers; Solar energy; Surge protection; Transformer windings; Arrester; Blockings; Circuit faults; Direct-current; Electro-magnetic transient; Ferroresonance; Malaysian power network; Malaysians; Neutral blocking device; Over-voltages; Power networks; Power system computer aided designs; Power system computer-aided design for electromagnetic transient including direct current; Surge; Timing circuits